Consistency in the Management of Tourist Attractions in Central Bangka Based on Regional Regulation Number 4 of 2019 concerning the Master Plan for Tourism Development in Central Bangka Regency for 2019-2025 - Didik Candra (Journal of Politica Governo, 2024)
The study of this research discusses the implementation of Regional Regulation Number 4 of 2019 concering the Tourism Development Master Plan of Central Bangka Regency for 2019-2025 in managing tourism objects in Central Bangka. Management of Tourism Objects in Central Bangka currently faces challenges that make te management of Tourism Objects less than optimal. The purpose of this research is to find out and describe the consistency of tourism objects management in Central Bangka based on Regional Regulation Number 4 of 2019 concerning the Tourism Development Master Plan of Central Bangka Regency 2019-2025 and to find out the challenges in implementing Regional Regulation Number 4 of 2019 concerning the Tourism Development Master Plan of Central Bangka Regency 2019-2025. The theory used in this research is the theory of Public Policy Implementation by Grindle. This research used the descriptive qualitative methode that used qualitative data and is elaborated into descriptive data. The data obtained will then be analyzed and described, the results of this study are able to find out the implementation of Regional Regulation Number 4 of 2019 concerning the Tourism Development Master Plan of Central Bangka Regency 2019-2025 in carrying out the management of Tourism Object in Central Bangka. In this case, it can be seen that there are several challenges faced by the Regional Government of Central Bangka Regency of implementing and managing Tourism Objects based on Regional Regulation Number 4 of 2019 concering Development Master Plan of Central Bangka Regency 2019-2025, including Regional Financial/Funding Capability, Human Resources, Lack of Tourism Promotion and Marketing Activities, Land Status, and Regional-Connected with Belitung. This makes the management of Tourism Objects in Cental Bangka less optimal and becomes obstructed.